2015
DOI: 10.1038/srep09434
|View full text |Cite
|
Sign up to set email alerts
|

Hsp60 response in experimental and human temporal lobe epilepsy

Abstract: The mitochondrial chaperonin Hsp60 is a ubiquitous molecule with multiple roles, constitutively expressed and inducible by oxidative stress. In the brain, Hsp60 is widely distributed and has been implicated in neurological disorders, including epilepsy. A role for mitochondria and oxidative stress has been proposed in epileptogenesis of temporal lobe epilepsy (TLE). Here, we investigated the involvement of Hsp60 in TLE using animal and human samples. Hsp60 immunoreactivity in the hippocampus, measured by Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Both direct CB1 receptor agonists and eCB degradation inhibitors are effective in controlling seizures in different models of epilepsy 29 , 30 , 39 , 40 , although proepileptic effects have been also reported 41 , 42 . Here, by using the MDA model of limbic seizures, in which repeated elicitation of PP stimulation in anaesthetised rats produces a progressive increase in afterdischarge duration of DG granule cells 43 , 44 , we found that both WIN and URB597 prevented the elongation of the MDA duration through a CB1 receptor-dependent mechanism, since this effect was reversed by administration of AM251. Furthermore, WIN, but not URB597, reduced the progressive decrease of the time to MDA onset.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Both direct CB1 receptor agonists and eCB degradation inhibitors are effective in controlling seizures in different models of epilepsy 29 , 30 , 39 , 40 , although proepileptic effects have been also reported 41 , 42 . Here, by using the MDA model of limbic seizures, in which repeated elicitation of PP stimulation in anaesthetised rats produces a progressive increase in afterdischarge duration of DG granule cells 43 , 44 , we found that both WIN and URB597 prevented the elongation of the MDA duration through a CB1 receptor-dependent mechanism, since this effect was reversed by administration of AM251. Furthermore, WIN, but not URB597, reduced the progressive decrease of the time to MDA onset.…”
Section: Discussionmentioning
confidence: 77%
“…Body temperature was maintained by a heating pad and a temperature controller unit (Temperature Control Unit HB 101/2, Letica Scientific Instruments). Surgical procedures were performed according to previous studies 43 , 72 . Briefly, field potentials were recorded from the hilus of the DG of the hippocampus (AP: −4.8 L: 2.5 V: 3.6) by stimulating the PP (AP: −7.9 L: 4.6 V: 3.4).…”
Section: Methodsmentioning
confidence: 99%
“…In neurodegenerative diseases, including AD, HSP70 is thought to induce protein conformational change in favor of nontoxic form [110]. In a separate study, both animals and human patients of temporal lobe epilepsy (TLE) had high HSP60 in their plasma and hippocampus; thus it has also been proposed as a biomarker of hippocampal stress having potential use for the diagnosis and TLE management [111]. Altogether, these reports indicate diverse function of HSPs depending on their type and disease condition.…”
Section: Damage-associated Molecular Patternsmentioning
confidence: 99%
“…Some HSPs were found to be localized in the synapse [60]. HSP60 is widely distributed in the brain and involved in neurodegenerative disorders [61]. When injured, HSP60 can be released to activate microglia in CNS [62].…”
Section: Resultsmentioning
confidence: 99%